Ethical Internalization and the Quest for Barakah: A Socio-Economic Study of Business Integrity among Muslim Entrepreneurs in East Java - Diana Wulandari; Muhammad Irsyad Baitussalam; Achmad Basofitrah; M.Afini Maulana; Abdul Ghofur; Imatun Sa’diah (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
This study examines the role of honesty (ṣidq) and barakah in the framework of Islamic business ethics among micro, small, and medium enterprises (MSMEs) in East Java. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and documentation involving selected Muslim business actors. The findings indicate that most MSME actors possess a basic understanding of honesty as a moral and religious obligation, reflected in transparency, fairness, and avoidance of fraud. Meanwhile, barakah is perceived as a spiritual value associated with inner peace, business continuity, and sustainable livelihood. However, these values are often understood normatively and not fully integrated into structured business strategies. The study also reveals that honesty positively influences consumer trust and loyalty, while barakah strengthens ethical consistency and long-term orientation. Nevertheless, challenges such as market competition, short-term profit orientation, and limited literacy in Islamic business ethics hinder consistent implementation. This study concludes that integrating honesty and barakah offers an alternative model for ethical and sustainable business practices. The findings contribute to the development of contextual Islamic business ethics and provide practical insights for strengthening ethical awareness among business actors.